Fairy tales and other stories as spiritual guides for children of war: an auto‐ethnographic perspective - Feuerverger, Grace (International journal of children's spirituality, 2010)
This article dares to suggest that the use of fairy tales as a pedagogical tool for children in and out of classrooms is and always will be about uplifting the human spirit: a way to survive; a pathway toward hope, especially for vulnerable children suffering from the trauma of war.